The nontrivial solutions for nonlinear fractional Schrödinger-Poisson system involving new fractional operator - HAMZA, Boutebba; LAKHAL, Hakim; KAMEL, Slimani; TAHAR, Belhadi (Advances in the theory of nonlinear analysis and its applications, 2023)
In this paper, we investigate the existence of nontrivial solutions in the Bessel Potential space for nonlinearfractional Schrödinger-Poisson system involving distributional Riesz fractional derivative. By using themountain pass theorem in combination with the perturbation method, we prove the existence of solutions.